Perjalanan Spiritual Biksu Thudong: Sebuah Refleksi atas Kerukunan Relasional dalam Wacana Dialog Lintas Agama di Indonesia - Candra Dvi Jayanti (Reformed Center for Religion and Society, 2024)
Thousands of kilometres travelled by 32 thudong monks from Thailand to Indonesia was not only a spiritual moment for the participants but also a historical event in Indonesian interfaith relations. Given the abundance of enthusiasm, this article aims to explain the purity of interfaith harmony created by local communities and Thai monks, who also contributed to promoting interfaith dialogue discourse among grassroots communities. By delving into the internet, a netnography approach is used to get a deeper and broader understanding of the events by comparing one digital document with another. In the interfaith encounters along the pilgrimage highway, both parties exhibited reciprocal behaviours of shared feelings and kindness that encouraged them to complete the ritual mission together. They were able to dismantle the religious barriers that frequently impede harmonious interfaith relations as a result of warm acceptance, hospitable interactions, and engaging dialogue onsite and via social media.